Associations Between School Environments, Policies and Practices and Children's Physical Activity and Active Transportation. (21st November 2021) - Blanchette, Sébastien; Larouche, Richard; Tremblay, Mark S.; Faulkner, Guy; Riazi, Negin A.; Trudeau, François
ABSTRACT: BACKGROUND: There is evidence of school‐level variability in children's active behaviors. This study investigated the associations between school environments, policies and practices, and children's physical activity (PA) and active school transportation (AST), in a school ecology context. METHODS: We recruited children (N = 1699, age = 10.2 ± 1.0 years, 55.0% girls) in 37 schools from 3 diverse regions of Canada. We then collected data using questionnaires (child, parent) and pedometers. In each school, an official completed a School Health Environment Survey. Multilevel regression models were used to examine associations with children's daily steps, and frequency and volume (frequency*distance) of AST. RESULTS: Between‐school variation ranged from 4.7% to 22.2% demonstrating that school environments are associated with children's active behaviors. None of the school environment variables were significantly associated with children's PA or frequency of AST. Nevertheless, their inclusion improved the PA model. Children's volume of AST increased in schools that reported more initiatives to promote AST. CONCLUSIONS: Our findings suggest that multiple components are needed to effectively promote active behaviors in children. Schools should determine the areas in which they can improve and assess the feasibility of implementing measures to make their school environments, policies, and practices more conducive to PA and AST.